Are certain CSA business models stimulating or stunting smallholder resilience and entrepreneurship? - Organisational Structures for Smallholder Resilience (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Agri-food systems in East and Southern Africa are undergoing rapid transformation due to climatic changes, urbanization and changing consumer preferences. As often underrepresented actors in agri-food systems, smallholder farmers and their farmer organizations struggle to adapt to and to absorb market, social and environmental shocks.